MESH DEPENDENCY IN NUMERIC MODELING FOR DETERMINATION OF THE FAILURE ZONE THICKNESS AROUND THE TUNNEL BASED ON HOEK BROWN CRITERIA - Permana, Aizil
The crush zone is an important component that can be used to assess and treat opening holes. The thickness of such crushed zones can be modeled using the finite element method in RS2 software. The modeling results obtained depend on the mesh used.